1980
DOI: 10.1159/000131472
|View full text |Cite
|
Sign up to set email alerts
|

Ring chromosome 15: phenotype, Ag-NOR analysis, secondary aneuploidy, and associated chromosome instability

Abstract: Cytogenetic analysis of a 15 month old girl evaluated for severe developmental delay and acral skeletal hypoplasia revealed a predominant 46, XX, r(15) karyotype. Prophase banding analysis showed minimal deletion of the ring chromosome (breakpoints pl2 and q26), while silver staining showed it to have an active nucleolus organizing region, multiple abnormal secondary configurations, and decreased satellite association. Although there was no spontaneous instability in the rest of the karyotype, gentian violet-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 15 publications
(20 reference statements)
4
17
0
1
Order By: Relevance
“…Dicentric, rod-shaped and interlocked ring abnormalities found in our case have been frequently reported in other ring chromosomes (Ledbetter et al, 1980, Zuffardi et al, 1980, Wyandt et al, 1982. Our case is the first to be described to have aneuploidy of ring chromosome 3.…”
Section: Discussionsupporting
confidence: 75%
“…Dicentric, rod-shaped and interlocked ring abnormalities found in our case have been frequently reported in other ring chromosomes (Ledbetter et al, 1980, Zuffardi et al, 1980, Wyandt et al, 1982. Our case is the first to be described to have aneuploidy of ring chromosome 3.…”
Section: Discussionsupporting
confidence: 75%
“…Some researchers found higher frequencies of monosomic cells without the ring chromosomes in fibroblast compared to lymphocyte cultures (Sparkes et al, 1967;Moore et al, 1973;Palmer et al, 1977;Peeden et al, 1983), while others found no significant differences between the two tissues (Valente et al, 1977;Ledbetter et al, 1980;Manouvrier-Hanu et al, 1988). Ledbetter et al (1980), however, found ring chromosomes 15 with an abnormal morphology in 9% of metaphase cells from lymphocyte cultures and in 20 and 24% of cells from fibroblast cultures in the third and tenth subculture, respectively, although it was not possible to know if these cells were formed de novo or were perpetuated in a clonal manner. Manouvrier-Hanu et al (1988) also found a higher frequency of cells with two ring chromosomes 9 in fibroblast compared to lymphocyte cultures.…”
Section: Discussionmentioning
confidence: 99%
“…These unstable chromosomes can lead to ring chromosome loss, producing monosomic cells, which may or may not be viable (Niss and Passarge, 1975;Ledbetter et al, 1980;Fang et al, 1995;Kosztolányi, 2009). Thus, ring chromosomes can vary in structure and number in an individual's somatic cells, resulting in a mosaic karyotype, a process called "dynamic tissue-specific mosaicism" (McDermott et al, 1977;Speevak et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, sister chromatid exchange within a ring produces dicentric or interlocked rings. These may lead to anaphase lag, hence aneuploidy, formation of micronuclei, pulverized chromosomes, and rings of different sizes, resulting in cells without a ring or with [Hoo et al, 1974;Ledbetter et al, 1980;C6te et al, 19813. It is possible that these ring derivatives may cause the rearrangement and/or interruption of other genes, including oncogene(s), which might be present on the particular chromosome involved.…”
Section: Discussionmentioning
confidence: 99%